Algebraic automata specification of common and distributed memory parallel programs - Doroshenko, A.Yu.; Tseytlin, G.E. (Інститут програмних систем НАН України, 2015)
Issues of automata and algebraic research ascending to fundamental works of V.М. Glushkov are covered, the retrospective review of the basic results received in the given area is given and their internal interrelations and perspective directions of development are established. There are considered algebrai dynamic models of parallel interaction of the sequential programs and algebraic algorithmic specifications associated with these models. The questions of discrete transformers above internal memory and conveyor calculations are stated and also theory of clones and tool means of synthesis of parallel algorithms and programs are considered.